Body fuel - food for sport (Peak Performance, 2005)
PROTEIN 1 - How much protein do athletes need - and how safe are high-protein diets? PROTEIN 2 - Optimum nutrition: it`s about much more than simply eating the right amount CARBOHYDRATE - Forget fancy supplements - carbs are even more important than you thought, for strength as well as endurance FAT - High-fat diets and endurance performance: is it time for a rethink? MINERALS 1 - Why magnesium matters to athletes MINERALS 2 - Could calcium be the new Holy Grail of sports nutrition? NUTRITION IN FOOTBALL - `Your role is to make sure there are no fat b******s in my team` RECOVERY - The post-exercise window of opportunity: why we need to start drawing the curtains WHAT THE SCIENTISTS SAY - When carbo-loading works for women WHAT THE SCIENTISTS SAY - Carbohydrates and perceived exertion WHAT THE SCIENTISTS SAY - It`s not just what you eat… WHAT THE SCIENTISTS SAY - Supercompensation only works once